Office of the citizen: a qualitative analysis of Twitter activity during the Lekki shooting in Nigeria's #EndSARS protests. Issue 15 (18th November 2022) - Dambo, Tamar Haruna; Ersoy, Metin; Auwal, Ahmad Muhammad; Olorunsola, Victor Oluwafemi; Saydam, Mehmet Bahri
ABSTRACT: In recent times, SNSs have been influential in re-shaping social movements. Not only do they allow access to cheaper and quicker mobilization resources for demonstrators, they also allow them to circumvent conventional communication networks to create their own narratives and thus gain communicative power. Therefore, the study explores the Twitter activities of the #EndSARS protesters in Nigeria on the night of the Lekki shooting with the specific objective of evaluating the role of influencers within the movement as well as establishing the various manifestations and expressions of anger or hope as tweeted by participants in the protests. The study discovered that users relied more on foreign media than local media for coverage while Nigerians in diaspora fueled information spreading about the protests on the night of the shooting.